Management Model to increase sales through Digital Marketing and the 4Ps of marketing in a craft brewery - Arana-Torres, Raul; Nieves-Asencio, Andrea; Elias-Giordano, Cynthia; Torres-Sifuentes, Carlos; Cespedes, Carlos (LACCEI, 2023)
Digital marketing is a tool that helps you to use new forms of digital and technological media, this way of marketing is important because in this world where the use of the internet and technology is increasing by leaps and bounds. The following article focuses on the craft brewery sector, alcohol consumption has a 63.4% market share making it one of the most consumed globally. On the other hand, there are the 4P's of marketing that are fundamental to implement a good marketing work in organizations. It is also known that the 4Ps, also known as marketing mix, refer to the product, price, promotion, and place; these allow to satisfy the needs of users and achieve the objectives set by each company. It is known that about 70% of customers stop buying from companies due to a lack of service, communication, and empathy because they do not provide the adequate service that customers require. Therefore, the following document will detail how the mix of these two tools is important to increase sales in a craft brewery.